Processing the Outcomes of Characters' Actions: The Impacts of Character Goals and Situational Context. Issue 5 (18th August 2018) - Chan, Greta C.; Magliano, Joseph P.; O'Brien, Edward J.
ABSTRACT: This study was conducted to investigate two factors that affect the processing of the outcomes of intentional actions. Participants read three-sentence stories that varied the presence of an explicit goal and the semantic association between the outcome and its situational context (i.e., physical or virtual location). The ease of processing outcomes (as measured by sentence reading times) was facilitated by having an explicitly stated goal (e.g., "X wanted a beer") that causally explained why an action (e.g., "X went to a bar") took place and by a high degree of contextual constraint between the action (e.g., "X went to a bar" as opposed to "X went to a restaurant") and the outcome (e.g., "X got a beer"). There was no evidence that the two factors interacted. These results suggest that readers monitor, in parallel, the associations of actions with the intentions of a character and the situational context in which those actions occur.